Maturity tools in the supply chain context: A framework proposal - Garrido, Susana; Correia, Elisabete; Aguiar, Marina Fernandes; Jugend, Daniel [UNESP]; Carvalho, Helena (Springer Nature, 2024)
The ability to recognize the gradual growth of a given supply chain considering a specific characteristic or factor by understanding its level of maturity is important for progress and benchmarking. These processes allow for a more effective and efficient identification of actions and directions to guide it toward excellence. This chapter aims to explore the theme of maturity tools for supply chainmanagement by suggesting a framework to guide the construction. Addressing maturity models in an integrated manner, this chapter helps students, researchers, and managers in assessing the current level of performance of their supply chains and making decisions about what can be done toward continuous improvement. In addition, practitioners may go deeper and apply the model presented or even develop a maturity model using the framework proposed as a guideline.
Keywords: Continuous improvement; Excellence; Maturity; Measurement; Supply chain